TEACHER’ OPINIONS AND EXPECTATIONS REGARDING TECHNOLOGY AND DESIGN COURSE OF ELEMENTARY EDUCATION FOR STAGE 2 (EXAMPLE OF BATMAN PROVINCE) - Sibel CENGİZHAN (Fırat University, 2019)
This study aims to identify the opinions and expectations of teachers in terms of Technology and Design course for the elementary education in second stage. Descriptive model is used in this study. As population, Technology and Design course teachers of central elementary schools in Batman province, associate of The Ministry of National Education, are used and sampling composes of; randomly selected 15 primary school teachers who are in charge of Technology design course in these schools. In order to collect data in the research, two different survey forms are developed regarding the determination of the vision (33 expressions) and expectations (20 expressions) of these teachers’. For the analysis of the data, average frequency, percentage and arithmetic values are calculated regarding the answers by teachers ' opinions and expectations. As a result of this study we can summarize that; according to the teacher's opinion, Technology and Design course has a positive contribution to the development of students, in contrast, it has also negative consequences such as; lack of a guiding resource book for students regarding this lesson, giving unnecessary details of scales of the program, lack of content in achieving the overall objectives, program’ nontrivial understandable structure, not clear, understandable, and achievable gains, activities are not applicable within the class. Regarding the teacher expectations it is concluded that they request; computer-assisted interactive lessons, activity products’ submission in a common exhibition on a provincial basis, providing in-service training to the teachers, parents, administrators frequently, a separate class of technology design.